Attempts to Use Thermal Imaging to Assess the Microbiological Safety of Poultry Meat in Modified Atmosphere Packaging - Edyta Lipińska; Katarzyna Pobiega; Kamil Piwowarek; Piotr Koczoń; Stanisław Błażejak (Applied Sciences)
Meat provides a favorable environment for the growth of microorganisms, so increasingly advanced methods are being sought to ensure the rapid detection of their presence and determine the degree of contamination. These measures are intended to ensure consumer health and reduce food losses. The aim of this study was to evaluate the suitability of a thermal imaging camera and FT-IR spectrophotometry for microbiological quality control of poultry meat. This study used poultry meat fillets packaged in a modified atmosphere and stored at 4 °C for 10 days. During the successive days of storage, the following were determined: the total number of microorganisms, the count of Enterobacteriaceae, the temperature of the samples tested using a thermal imaging camera, and the spectral data contained in the spectra recorded by the FT technique of IR spectroscopy. The results were analyzed using Tukey’s test in the STATISTICA 13.3 statistical program with an assumed significance level of α ≤ 0.05. Spectral data obtained by the FT-IR method were subjected to interpretation using the T.Q. Analyst 8 program. This study found that the number of microorganisms increased between the 2nd and 10th days of storage for the poultry meat samples of four log CFU/g, leading to a temperature increase of 2.61 °C, and also, the intensities and frequencies of selected IR bands generated by vibrations of various groups of atoms changed, including functional groups present in the compounds contained in the tested samples. It was shown that modern techniques such as FT-IR spectroscopy and thermal imaging cameras have significant potential applications in the food industry for assessing the microbiological quality of food.